Penggunaan CCTV Untuk Meningkatkan Kepatuhan Petugas Pelayanan Dalam Pemilahan Limbah di Rumah Sakit: The Use of CCTV to Improve Service Officer Compliance in Waste Sorting in Hospital - Ria Ismayani Ni Putu; Mochammad Choirul Hadi; I Wayan Sali; Iin Indayani (Jurnal Kesehatan Lingkungan (JKL), 2026)
Title:  The Use of CCTV to Improve Service Officer Compliance in Waste Sorting in Hospital Background: Hospital waste segregation is an important part of managing medical, non-medical, and domestic waste to prevent environmental pollution and health risks. The purpose of this study is to analyze the differences in compliance of service personnel in hospital waste segregation before and after supervision by environmental health officers using assistance tools such as CCTV media. Method: The type of research used a quasi-experimental design with a pre and post-test without control. The number of samples that met the inclusion and exclusion criteria in this study was 49 people with positions as service officers. Statistical tests to analyze differences before and after supervision were conducted using the Wilcoxon test. Result: The research results showed that before supervision, the non-compliant category consisted of 25 people (51.0%), fairly compliant 20 people (40.8%), and compliant 4 people (8.2%). After supervision, the non-compliant category consisted of 5 people (10.2%), fairly compliant 20 people (40.8%), and compliant 24 people (49.0%). The Wilcoxon test results showed a p-value < 0.05, indicating a significant difference in compliance before and after supervision. Conclusion: It can be concluded that there was an increase in the compliance of service personnel in terms of waste segregation, from 4 people (8.2%) to 24 people (49.0%) after supervision by environmental health officers using CCTV media. Keywords:  waste sorting; compliance; CCTV monitoring; hospital